2018
DOI: 10.31461/ybpd.486928
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Training Intensity and Knowledge Sharing Among Banking Sector Employees in Turkey: Examining the Moderating Role of Intrinsic Motivation and Self-Efficacy

Abstract: The aim of the present study is to show the links between the domains of knowledge management and human resources management. This study was conducted among employees from multiple organizations (within different organizational frameworks) in the banking sector in Turkey to examine the relationship between perceived training intensity (PTI) and knowledge sharing considering intrinsic motivation and self-efficacy as the moderating variables. Data was collected from 497 employees working in four different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Thus, every time there is an increase in the knowledge sharing self-efficacy (X1) of Bank Syariah Mandiri in Indonesia, the knowledge sharing behavior (Y2) of Bank Syariah Mandiri in Indonesia will also increase. In line with the research that has been carried out by Bilginoğlu and Yozgat (2018), Chen and Hung (2010), Hsu et al (2007), Kwahk & Park (2016), Pan and Zhang (2018), Safdar et al (2021), Islam et al (2018) and Zhang et al (2016) show that knowledge sharing self-efficacy has a positive effect on knowledge sharing behavior. The results of this study indicate that the middle managers of Bank Syariah Mandiri in Indonesia through their knowledge sharing self-efficacy will gain confidence in what they can do and they will think that their expertise can improve work efficiency which can increase productivity.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, every time there is an increase in the knowledge sharing self-efficacy (X1) of Bank Syariah Mandiri in Indonesia, the knowledge sharing behavior (Y2) of Bank Syariah Mandiri in Indonesia will also increase. In line with the research that has been carried out by Bilginoğlu and Yozgat (2018), Chen and Hung (2010), Hsu et al (2007), Kwahk & Park (2016), Pan and Zhang (2018), Safdar et al (2021), Islam et al (2018) and Zhang et al (2016) show that knowledge sharing self-efficacy has a positive effect on knowledge sharing behavior. The results of this study indicate that the middle managers of Bank Syariah Mandiri in Indonesia through their knowledge sharing self-efficacy will gain confidence in what they can do and they will think that their expertise can improve work efficiency which can increase productivity.…”
Section: Resultssupporting
confidence: 85%
“…Islamic banking requires individuals who have knowledge sharing self-efficacy which can be manifested in a person’s belief that their knowledge can help solve problems and share work-related ideas. Research that has been carried out by Bilginoğlu and Yozgat (2018), Pan and Zhang (2018), Safdar et al (2021), and Zhang et al (2016) showed that knowledge sharing self-efficacy has a positive effect on knowledge sharing behavior, this finding provides support that individuals with high self-efficacy tend to try hard in doing tasks and experience better positive emotions (Bandura, 1977). Thus, this study hypothesizes that:…”
Section: Literature Reviewmentioning
confidence: 73%
“…There is a positive relationship between self-efficacy and knowledge sharing (Bilginoglu and Yozgat, 2018;Castaneda et al, 2016). Safdar et al (2021), based on a systematic review, concluded that self-efficacy is a predictor of knowledge sharing.…”
Section: Self-efficacymentioning
confidence: 99%